(untitled) (Plant Tissue Culture and Biotechnology, 2013)
Esmeralda clarkei Rchb.f. (Orchidaceae), an epiphytic orchid native to Nepal with high ornamental value grows from cool to intermediate climatic conditions with medium amount of light. In an attempt to preserve this important orchid by establishing an efficient in vitro regeneration protocol using seed culture was conducted. MS with BAP and NAA alone or in combination were used. In MS protocorms developed within 16 weeks followed by seedling development in 25 weeks of seed culture. Presence of BAP (0.5 mg/l) in MS improved seed germination by protocorm formation and seedling development in 17 and 26 weeks of seed culture, respectively. In 0.5 mg/l NAA supplemented media, development of protocorms was observed in 18 weeks and seedling growth was observed in 26 weeks of seed culture. Protocorm and seedling development were was delayed in other media. DOI: http://dx.doi.org/10.3329/ptcb.v22i2.14197 Plant Tissue Cult. & Biotech. 22(2): 107-111, 2012 (December)